The management of vulval itching caused by benign vulval dermatoses. (24th October 2017) - Nunns, David; Simpson, Rosalind; Watson, Andrew; Murphy, Ruth
Abstract : Key content: This article will cover key points in patient assessment, vulval examination and treatment of vulval disease, specifically dermatological conditions. Often, simple measures can benefit the patient (e.g. use of emollients). However, many women have complex disease with more than one condition, so careful assessment and individualised management is essential. Some gynaecologists have unmet training needs in the assessment and management of vulval skin disease. It is important to assess patients and then refer difficult cases and non‐responders to a vulval service for a multidisciplinary opinion. Learning objectives: To increase skills in patient assessment, vulval examination and treatment of common vulval diseases. To improve clinical outcomes for women by increasing basic and intermediate knowledge and skills of vulval disease according to the national evidence base. Ethical issues: Clinicians managing vulval disease must be sensitive and willing to ask women about sexual problems associated with their disease. All clinicians, regardless of experience or level of seniority, should have an understanding of the relevant conditions underlying these symptoms.